Increasing of the bacteriostatic effects of HCl tetracycline–polyethylene glycol 6000 – tween 80 (PT) - Riswaka Sudjaswadi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The antibacterial effect of HCl tetracycline – polyethylene glycol-tween 80 (PT) solid dispersion in the mole fraction of 0,1; 0,5; 0,7; 0,9; and 1,0 on Saphylo coccus aureus and on Escherichia coli had been studied by using the diffusion methods, in order to obtain the roles of PT on the drug penetration through the membrane and on the bacteriostatic effects.The results shown that the effects on Staphylococcus aureus in the mole fraction of 0,1; 0,5; 0,9 seemed to be the same when using the diffusion method (hole systems), whilst using the diffusion method (paper disc), all agents performed the increased effects in the mole fraction of 0,5; 0,7; and 0,9; in comparison with the mol fraction of 1,0, respectively.It had been concluded that PT expressed the increased effects of HCL tetracycline from 100,00 % up to 124,54 % on Staphylococcus aureus, and 108,90 % to 127,27 % on Escherichia coli.Key words : solid dispersion, bacteriostatic, HCl tetracycline, PEG-tween 80.